"If the Lesson Is Not Going as Planned, Learn From It and Adapt": Examining a Hybrid Field Experience. Issue 3 (3rd July 2019) - Seglem, Robyn
Abstract: This article examines the possibilities of supplementing field experiences with digitally mediated third spaces as a way to foster relationships between urban youth and middle-class teacher candidates. Pairing these experiences with a well-remembered events framework, this study explores how relationships built primarily through digital tools influence preservice teachers' understanding of teaching. Drawing upon 4 months of data, composed of preservice teachers' reflections, this study examines the experiences identified by preservice teachers as memorable and unpacks the lessons digitally mediated experiences provide. This study concludes by pointing to technology as a potential solution for helping teacher education institutions create meaningful experiences between preservice teachers and youth in urban centers.